Pendampingan Pembelajaran Anak di RA Darussalam melalui Manajemen Controlling di Pringgondani, Bantur-Malang - Eva Siti Rohmah; Muhammad Husni (Lembaga Penerbitan dan Publikasi Ilmiah, 2024)
This study aims to analyze and evaluate the effectiveness of children's learning assistance at RA Darussalam through the implementation of controlling management in Krajan Pringgodani, Bantur, Malang. The method used in this research is a qualitative approach with data collection techniques through observation, interviews, and documentation. The results show that the controlling management applied at RA Darussalam plays an important role in improving the quality of children's learning. The assistance includes structured planning, supervision, evaluation, and follow-up. Through this controlling management, teachers can effectively monitor student progress and provide appropriate interventions according to each child's needs. The research also found that the involvement of parents and the surrounding community supports the success of this assistance program. With good cooperation between teachers, parents, and the community, children gain a more holistic and supportive learning environment. The findings indicate that controlling management focuses not only on academic aspects but also on children's social and emotional development. The controlling management model applied at RA Darussalam shows flexibility in adjusting to the individual needs of students, creating a more inclusive and child-centered learning process. Therefore, this model can serve as a reference for other early childhood education institutions in efforts to improve the overall quality of learning. In conclusion, the implementation of controlling management at RA Darussalam significantly contributes to enhancing the quality of learning and can be adopted by other institutions with relevant adjustments.